2000
DOI: 10.1007/s004240000388
|View full text |Cite
|
Sign up to set email alerts
|

Functional incorporation of exogenous proteins into the Xenopus oocyte membrane does not depend on intracellular calcium increase

Abstract: Fusion of membranes occurs in diverse biological events and, in most cases, Ca2+ greatly augments its rate. The aim of this work was to study the role played by Ca2+ when transplanting exogenous proteins into Xenopus oocyte membranes. Lipid vesicles carrying nicotinic acetylcholine (ACh) receptors (nAChRs) from Torpedo electroplaques were injected into oocytes. The time course of nAChR incorporation was assessed by recording ACh-evoked currents at different times from injection. An incorporation peak was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
(20 reference statements)
1
4
1
Order By: Relevance
“…This conclusion seems plausible because the protein-containing vesicles are the limiting factor for incorporation and are not replenished after the initial injection. Interestingly, the timecourse for functional Shaker channels is similar to that reported for transplanted lipid vesicles containing nicotinic acetylcholine receptors from Torpedo electroplaques21.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This conclusion seems plausible because the protein-containing vesicles are the limiting factor for incorporation and are not replenished after the initial injection. Interestingly, the timecourse for functional Shaker channels is similar to that reported for transplanted lipid vesicles containing nicotinic acetylcholine receptors from Torpedo electroplaques21.…”
Section: Resultssupporting
confidence: 76%
“…While we did not explicitly examine the mechanistic details of oligomerization in this communication, several groups have shown that proteins can be processed and oligomerize during cell-free preparation and functionally incorporate into artificial bilayers resembling proteins from a native membrane262728. Additionally, at present we cannot state how our synthesized proteins incorporate into the oocyte membrane (constitutive or non-constitutive pathway) however, evidence from Gal and Morales points to a slow constitutive mechanism independent of intracellular calcium21. Additional experiments using our approach are needed to fully examine the method of channel incorporation.…”
Section: Discussionmentioning
confidence: 91%
“…Incorporation of the exogenous channels modified the membrane properties of the recipient cells, allowing us to estimate by electrophysiological means that 62% of the injected oocytes showed a successful functional transplantation of hSM channels. This percentage was clearly lower than that obtained for nicotinic acetylcholine receptors or ClC-0 channels from the Torpedo electroplaque, in which the value obtained was over 90% [16,23,30]. This discrepancy could be due to differences in the lipid composition of the injected vesicles, in the type or number of channels injected, and/ or in the preservation of the functional activity of the injected proteins.…”
Section: Discussioncontrasting
confidence: 79%
“…Lipid bilayers can fuse together passively in the absence of Ca 2+ , but many membrane-fusion processes such as neurotransmitter and hormonal secretion, myoblast fusion, membrane resealing, and nuclear vesicle fusion in Xenopus eggs either require or are boosted by an increase in the intracellular Ca 2+ concentration ([Ca 2+ ] i ). The role played by [Ca 2+ ] i in the efficacy of transplanting purified proteins into the Xenopus oocyte membrane has been explored [ 74 ]. In these experiments, [Ca 2+ ] i was decreased by using Ca 2+ chelators, either through preincubating oocytes with 1,2-bis (2-aminophenoxy)ethane N,N,N′,N′-tetraacetic acid acetoxymethyl ester (BAPTA-AM) or loading the cells with ethyleneglycol-bis (β-aminoethylether)-N,N,N′,N′-tetraacetic acid (EGTA), and several hours later, these cells were injected with proteoliposomes bearing nAChRs.…”
Section: Transplant Of Fully Processed Membrane Proteins To the ...mentioning
confidence: 99%
“…In these experiments, [Ca 2+ ] i was decreased by using Ca 2+ chelators, either through preincubating oocytes with 1,2-bis (2-aminophenoxy)ethane N,N,N′,N′-tetraacetic acid acetoxymethyl ester (BAPTA-AM) or loading the cells with ethyleneglycol-bis (β-aminoethylether)-N,N,N′,N′-tetraacetic acid (EGTA), and several hours later, these cells were injected with proteoliposomes bearing nAChRs. Effective Ca 2+ chelation was proven by the lack of oscillatory Ca 2+ -dependent Cl − currents after superfusing these cells with serum, which activates lysophosphatidic acid receptors of the oocyte membrane [ 75 , 76 ] and, subsequently, the phosphatidylinositol cascade ( Figure 3 ; [ 74 ]). These experiments evidenced that both the control and Ca 2+ -chelated oocytes presented similar ACh-elicited currents ( I ACh s), indicating that the fusion of the proteoliposome vesicle with the cellular membrane was not dependent on the local increases of [Ca 2+ ] i .…”
Section: Transplant Of Fully Processed Membrane Proteins To the ...mentioning
confidence: 99%